(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This research aims to explore and analyse the restoration of the Qur’an-based character education system at SMAIT (Integrated Islamic Senior High School) Nurul Fajri as an effort to actualize the progress of civilization. The main focus of this research is to understand how the values of the Qur’an are integrated into the educational curriculum to form the character of students with noble character, as well as their impact on the moral and social development of students. The research method used is a qualitative approach with a case study design, which allows the researcher to gain an in-depth understanding of the implementation of the character education program at SMAIT Nurul Fajri. Data is collected through in-depth interviews, observations, and analysis of relevant documents. The results of the study show that the integration of Qur’an values in education at SMAIT Nurul Fajri has a positive impact on the formation of students’ character. This program has succeeded in creating a learning environment that is conducive to the moral and ethical development of students, as well as assisting them in internalizing the values of the Qur’an in daily life. In addition, the holistic approach applied includes academic, spiritual, and social aspects, all of which contribute to shaping students who have integrity, noble character, and are ready to face the challenges of modern civilization.